2000
DOI: 10.1103/physrevb.61.12045
|View full text |Cite
|
Sign up to set email alerts
|

Time-delayed charge-injection effects on photocurrent shape in a double layer

Abstract: Transient photocurrents of double-layer structures were simulated by a random walk through a cubic lattice in this work. The canonical technique of time of flight was simulated to find the characteristics of the photocurrents shape when each layer had a different mobility. The results reproduce the main features of the experimental data from similar real experiments reported in the literature. Also, the origin of the peak shape of photocurrents is discussed and it is shown that it is related to a stochastic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Instead, we investigate here the idea that the flat plateau, universality, and the approximately t −2 current decay in the tails, as well as the cusps that occasionally occur, may all be caused by a delay of the charge carriers which arises, not just from traps right at the interface but from a trap-rich surface layer that penetrates from the interface into the bulk of the film. The idea that cusps may be caused by the presence of a surface layer in MDPs that has different trapping characteristics than the bulk has been suggested before. Tyutnev, et al , have suggested that there is a thin, approximately one micrometer thick, trap-rich surface layer that causes the charge to be delayed before it crosses into the bulk. Indeed, according to this proposal it is the interplay between the depth of the charge generation region and the thickness of the surface region that determines the particular transient shape seen in any given time-of-flight measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we investigate here the idea that the flat plateau, universality, and the approximately t −2 current decay in the tails, as well as the cusps that occasionally occur, may all be caused by a delay of the charge carriers which arises, not just from traps right at the interface but from a trap-rich surface layer that penetrates from the interface into the bulk of the film. The idea that cusps may be caused by the presence of a surface layer in MDPs that has different trapping characteristics than the bulk has been suggested before. Tyutnev, et al , have suggested that there is a thin, approximately one micrometer thick, trap-rich surface layer that causes the charge to be delayed before it crosses into the bulk. Indeed, according to this proposal it is the interplay between the depth of the charge generation region and the thickness of the surface region that determines the particular transient shape seen in any given time-of-flight measurement.…”
Section: Introductionmentioning
confidence: 99%